Insight to Improve α-L-Arabinofuranosidase Productivity in Pichia pastoris and Its Application on Corn Stover Degradation - Zheng, Fengzhen; Liu, Junquan; Basit, Abdul; Miao, Ting; Jiang, Wei (Frontiers in Microbiology, 2018)
α-L-arabinofuranosidase (ARA) with enhanced specific activity and in large amounts, is needed for a variety of industrial applications. To improve ARA production with engineered methylotrophic yeast Pichia pastoris, a genetically modified ara gene from Aspergillus niger ND-1 was investigated. Through codon optimization and rational replacement of α-factor signal peptide with the native propeptide (MFSRRNLVALGLAATVSA), ARA production was improved from 2.61 ± 0.13 U/mL to 14.37 ± 0.22 U/mL in shaking flask culture (a 5.5-fold increase). Results of N-terminal sequencing showed that secreted active ARA of recombinant strain p-oARA had theoretical initial five amino acids (GPCDI) comparable to the mature sequences of α-oARA (EAEAG) and αp-oARA (NLVAL). The kinetic values have been determined for ARA of recombinant strain p-oARA (Vmax = 747.55 μmol/min/mg, Km = 5.36 mmol/L), optimal activity temperature 60°C and optimal pH 4.0. Scaling up of ARA production by p-oARA in a 7.5-L fermentor resulted in remarkably high extracellular ARA specific activity (479.50 ± 12.83 U/mg) at 168 h, and maximal production rate 164.47 ± 4.40 U/mL. In studies of corn stover degradation activity, degree of synergism for ARA and xylanase was 32.4% and enzymatic hydrolysis yield for ARA + xylanase addition was 15.9% higher than that of commercial cellulase, indicating significant potential of ARA for catalytic conversion of corn stover to fermentable sugars for biofuel production.